Legal basis for providing legal aid to a detained person in the context of international standards and practice of the European Court of Human Rights - M. М. Kolomoitsev (Bulletin of Kharkiv National University of Internal Affairs)
Based on the analysis of theoretical approaches to the essence of the institute of detention of a person, the article substantiates the position that detention is a procedural action which has a temporary restrictive nature of the rights of a person who was detained during the commission or attempted commission of a criminal offence, immediately after the commission of a criminal offence or during the continuous prosecution of a person suspected of a criminal offence, and which aims to ensure further pre-trial investigation, clarification of the circumstances of the event which occurred.